Antitumor Activity and Antioxidant Status of the Methanol Extract of Careya arborea Bark Against Dalton's Lymphoma Ascites-Induced Ascitic and Solid Tumor in Mice - Senthilkumar Natesan; Shrishailappa Badami; Santoshkumar H. Dongre; Ashok Godavarthi (Elsevier, 2007)
Based on the ethnomedical use of Careya arborea Roxb bark in the treatment of tumors, the present study was carried out to evaluate the anticancer potentials against Dalton's lymphoma ascites (DLA)-induced ascitic and solid tumors. The methanol extract of its bark given orally to mice at the dose of 250 or 500 mg/kg body weight for 10 days caused significant reduction in percent increase in body weight, packed cell volume, and viable tumor cell count when compared to the mice of the DLA control group. Restoration of hematological and biochemical parameters towards normal was also observed. Histological observations of liver and kidney also indicated repair of tissue damage caused by tumor inoculation. The extract at the dose of 5 or 25 mg/kg body weight given i.p. daily for 14 days significantly reduced the solid tumor volume induced by DLA cells. Keywords:: Careya arborea, antitumor, antioxidant, hepatoprotective, solid tumor